Investigating the therapeutic role and molecular biology of curcumin as a treatment for glioblastoma. (July 2016) - Rodriguez, Gregor A.; Shah, Ashish H.; Gersey, Zachary C.; Shah, Sumedh S.; Bregy, Amade; Komotar, Ricardo J.; Graham, Regina M.
Objectives: Despite the aggressive standard of care for patients with glioblastoma multiforme, survival rates typically do not exceed 2 years. Therefore, current research is focusing on discovering new therapeutics or rediscovering older medications that may increase the overall survival of patients with glioblastoma. Curcumin, a component of the Indian natural spice, turmeric, also known for its antioxidant and anti-inflammatory properties, has been found to be an effective inhibitor of proliferation and inducer of apoptosis in many cancers. The goal of this study was to investigate the expanded utility of curcumin as an antiglioma agent. Methods: Using the PubMed MeSH database, we conducted a systematic review of the literature to include pertinent studies on the growth inhibitory effects of curcumin on glioblastoma cell lines based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: A total of 19 in vitro and five in vivo studies were analyzed. All of the studies indicated that curcumin decreased glioblastoma cell viability through various pathways (i.e. decrease in prosurvival proteins such as nuclear factor κB, activator protein 1, and phosphoinositide 3 kinase, and upregulation of apoptotic pathways like p21, p53, and executor caspase 3). Curcumin treatment also increased animal survival compared with control groups. Conclusions: Curcumin inhibits proliferation and induces apoptosis in certain subpopulations of glioblastoma tumors, and its ability to target multiple signaling pathways involved in cell death makes it an attractive therapeutic agent. As such, it should be considered as a potent anticancer treatment. Further experiments are warranted to elucidate the use of a bioavailable form of curcumin in clinical trials.